2015
DOI: 10.1002/app.42178
|View full text |Cite
|
Sign up to set email alerts
|

In vivo bioactivity of herbal‐drug‐incorporated nanofibrous matrixes

Abstract: Aloe-vera-incorporated polycaprolactone nanofibrous matrixes were prepared by an electrospinning method. These developed matrixes were evaluated for their water absorption capacity, water vapor permeability, and contact angle, and, in an in vivo animal model, wound-healing ability. The incorporation of the herbal drug made the matrixes hydrophilic with improved water retention and permeability properties. The in vivo studies were carried out in a rat model and showed improved results with respect to healing. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The PVA+SBA-15+curcumin composite nanofiber with an average contact angle of 48.2°±1.4 was highly hydrophilic compared to PVA and PVA+curcumin, which was due to the combination of PVA and SBA-15 [39,40] as both are hydrophilic in nature (table 4). Moreover, a moist wound is known to maintain both optimal wound temperature and reduced infection rate and scarring compared to dry wounds [41]. Thus, the synthesized nanofiber with hydrophilicity enables good potential for cell-biomaterial interaction and forms a suitable material for wound dressing.…”
Section: Contact Angle Measurementmentioning
confidence: 99%
“…The PVA+SBA-15+curcumin composite nanofiber with an average contact angle of 48.2°±1.4 was highly hydrophilic compared to PVA and PVA+curcumin, which was due to the combination of PVA and SBA-15 [39,40] as both are hydrophilic in nature (table 4). Moreover, a moist wound is known to maintain both optimal wound temperature and reduced infection rate and scarring compared to dry wounds [41]. Thus, the synthesized nanofiber with hydrophilicity enables good potential for cell-biomaterial interaction and forms a suitable material for wound dressing.…”
Section: Contact Angle Measurementmentioning
confidence: 99%
“…Conversely, CS_PEO and CS_AV_PEO layers presented WCA values of 75.58° ± 12.57° and 69.06° ± 3.78° which are characteristic of moderate hydrophilic materials. Such WCA values can be explained by the presence of natural polymers (CS and AV) that have functional groups like amides, esters, and hydroxyl groups which confer hydrophilic character to the bottom layer [ 81 , 82 ]. During the wound healing process, hydrophilic materials are able to provide moist environments, that enhance the healing process [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…The PVA + 3% MC sample showed a ZOI for S. aureus of 1.3 ± 0.3 mm, which was greater compared to the inhibition zones observed for PVA + 1% MC (0.6 ± 0.1 mm), PVA + 2% MC (0.9 ± 0.2 mm), and PVA (0.5 ± 0.08 mm). Similarly, the anti-bacterial activity described by Esath Natheer et al in 2012 [73] and Selvam et al in 2008 [22,23] for MC extract also reported the observation of a higher ZOI for a higher concentration of the tested pathogens. The inhibitory results for PVA, PVA + 1% MC, PVA + 2% MC, and PVA + 3% MC nanofibrous scaffolds for the gram-negative pathogen E. coli were 0.4 ± 0.07, 0.6 ± 0.1, 0.9 ± 0.2, and 1.3 ± 0.3 mm respectively.…”
Section: Anti-bacterial Assaymentioning
confidence: 52%